Linear Polarization Characteristics Within the Rosh HaNikra Mid-Littoral Cave, Israel - Tzabari, Masada; Mayer Mayron, Danielle; Iluz, David; Dubinsky, Zvy; Haspel, Carynelisa (Frontiers in Marine Science, 2018)
Light polarization characteristics, i.e., degree of linear polarization (DoLP) and angle of linear polarization (AoLP)E- vector angle, including annual and daily patterns, were documented in the depth of the littoral cave system of Rosh HaNikra on the northern Mediterranean shore of Israel (33° 5′ 35.24″ N, 35° 6′ 17.16″ E), based on light intensity sampled through polarizing filters at different hours of the day on different days of the year. . This is the first study to investigate the state of light polarization in such a unique habitat in which photosynthetic organisms, such as cyanobacteria, microalgae and macroalgae thrive. Such organisms play an essential ecological role as the energy base for the cave’s fauna. .Using these two methods, we found unique winter polarization characteristics within the cave, including high values of DoLP in the morning and at noon, reaching 50%, and nearly constant AoLP throughout the day. Given the low levels of light intensity that typically exist within the cave in the winter months, the relatively high DoLP and the nearly constant AoLP throughout the day may play a significant role in improving the ability of photosynthetic organisms within the cave to harvest light by orienting their light-harvesting receptors with respect to the AoLP. Using the polarization photograph analysis method, we were able to determine the polarization characteristics originating from the sky, reflection off of the far sea surface, and reflection off of (including refraction into followed by refraction out of) the cave wall separately. The maximum DoLP values originating from the sky, far ocean, and cave walls were found to be 27%, 50%, and 35%, respectively. The lowest daily variation in AoLP was that of light reflecting off the cave walls. The present pioneering study lays the foundation for any subsequent study of the role of light polarization in the distribution of the algal flora on the cave walls in and out of the water in the Rosh HanNikra cave and in sea caves in general.